Characteristics Of Goat's Milk Yoghurt Based Jackfruit And Cempedak - Sampurno, Adi; Cahyanti, Antonia Nani; Nofiyanto, Erwin (Universitas Semarang, 2020)
This study aims to determine change of total Lactic Acid Bacteria (LAB), pH, total lactic acid (titrated acid), viscosity, total sugar and total reducing sugar goat milk yogurt with the addition of jackfruit and cempedak fruit pulp using a commercial LAB starter Lactobacillus bulgaricus and Streptococcus thermophillus. The research design was a completely randomized design (CRD) with one factor, the treatment was the addition of : P1 = 5% jackfruit pulp, P2 = 10% jackfruit pulp, P3 = 5% cempedak fruit pulp, P4 = 10% cempedak fruit pulp) with 5 repetitions. The results showed that the total LAB in accordance with the Indonesian National Standard (SNI) 2981: 2009; decreased pH value, total lactic acid; increase in viscosity, total sugar and total reducing sugar goat milk yogurt based jackfruit and cempedak.